Parental Pre-knowledge Enhances Guidance During Inquiry-Based Family Learning in a Museum Context: An Individual Differences Perspective - Franse, Rooske K.; Van Schijndel, Tessa J. P.; Raijmakers, Maartje E. J. (Frontiers in Psychology, 2020)
Effective interaction and inquiry are an essential source for children’s learning about science in an informal context. This study investigated the effect of parental pre-knowledge on parent-child interactions (manipulations, parent talk and child talk) during an inquiry activity in NEMO Science Museum in Amsterdam. The sample included one hundred and five parent-child dyads (mean children’s age = 10.0 years). Half of the couples were randomly assigned to the experimental group in which, without the child’s knowledge, the parent was shown the task’s solution prior to the inquiry activity. Results show that parental pre-knowledge affected the way parents interacted and inquired with their child. Compared to parents without pre-knowledge, parents with pre-knowledge inquired longer, posed more open-ended wh-questions and closed questions and less often interpreted results. Children of parents with pre-knowledge more often described evidence and interpreted results, more often manipulated alone, and solved the task more accurately. These results indicate that parental pre-knowledge brings about parents’ scaffolding behavior. In addition, it was studied how individual differences of parents and children relate to parent-child interaction. Results show that children’s self-reported inquiry attitude was related to their conversation during inquiry, such that they asked fewer closed questions and more open-ended questions. Children’s gender affected the cooperation between parent and child, parents more often manipulated together with boys than with girls, and girls more often manipulated alone. Fathers with pre-knowledge, but not mothers, let their child manipulate more by oneself than fathers without pre-knowledge. This study shows that more knowledge about an exhibit improves a parent's scaffolding behavior in a science museum. Results are discussed in the context of museum practice.